Perancangan Aplikasi Web Asisten Dosen dengan Metode Design Thinking - Chung, Cecillia; Lauro, Manatap Dolok (Politeknik Harapan Bersama, 2025)
Teaching assistants (TAs) play a crucial role in supporting practical learning processes. However, TA management often encounters challenges in class and teaching time allocation, TA attendance recapitulation, and end-of-semester evaluations. To address these issues, a system that facilitates the management of practical sessions involving TAs is necessary. This web application system is designed to streamline task management, class scheduling, material collection, attendance tracking, and TA evaluations at the end of each semester. Furthermore, supporting features such as an integrated dashboard and automated notifications can enhance the delivery of practical services to students. This research employs the Design Thinking methodology, an innovative, user-centered design approach, to develop solutions that meet user needs. Through the stages of empathize, define, ideate, prototype, and test, the resulting web application not only simplifies practical management but also improves the user experience for both lecturers and TAs. Based on a questionnaire administered to 20 teaching assistants, usability testing of the web application using the System Usability Scale (SUS) method yielded an average score of 77.25, which falls under the 'good' category. Thus, this web application is expected to serve as an innovative solution that fosters a more flexible and integrated teaching and learning environment.